Who Benefits from Government Expenditure? / A Case Study of Columbia - Selowsky Marcelo (Oxford University Press, 1979)
Governments can improve the distribution of income and also can eradicate extreme poverty by changing the composition and direction of their public expenditure. Foreword, Acknowledgements, Introduction and Summary, Background and Main Results, The Distribution of Income, The Distribution of Public Subsidies, The Distribution of Public Subsidies for Health, The Distribution of Consumption of Public Utility Services: Electricity and Piped Water and Sewerage, Statistical Appendix, References, Index.